Task-Irrelevant Expectation Violations in Sequential Manual Actions: Evidence for a “Check-after-Surprise” Mode of Visual Attention and Eye-Hand Decoupling - Foerster, Rebecca M. (Frontiers in Psychology, 2016)
When performing sequential manual actions (e.g., cooking), visual information is prioritized according to the task determining where and when to attend, look, and act. In well-practiced sequential actions, long-term memory (LTM)-based expectations specify which action targets might be found where and when. We have previously demonstrated (Foerster and Schneider, 2015b) that violations of such expectations that are task-relevant (e.g., target location change) cause a regression from a memory-based mode of attentional selection to visual search. How might task-irrelevant expectation violations in such well-practiced sequential manual actions modify attentional selection? This question was investigated by a computerized version of the number-connection test. Participants clicked on nine spatially-distributed numbered target circles in ascending order while eye movements were recorded as proxy for covert attention. Target’s visual features and locations stayed constant for 65 prechange-trials, allowing practicing the manual action sequence. Consecutively, a task-irrelevant expectation violation occurred and stayed for 20 change-trials. Specifically, action target number 4 appeared in a different font. In 15 reversion-trials, number 4 returned to the original font. During the first task-irrelevant change trial, manual clicking was slower and eye scanpaths were larger and contained more fixations. The additional fixations were mainly checking fixations on the changed target while acting on later targets. Whereas the eyes repeatedly revisited the task-irrelevant change, cursor-paths remained completely unaffected. Effects lasted for 2-3 change trials and did not reappear during reversion. In conclusion, an unexpected task-irrelevant change on a task-defining feature of a well-practiced manual sequence leads to eye-hand decoupling and a “check-after-surprise” mode of attentional selection.